2019
DOI: 10.1002/pola.29498
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyhedral oligomeric silsesquioxane‐containing block copolymer with well‐controlled stereoregularity

Abstract: Preparation of functional domains with a spacing of 10 nm is a benchmark set to fabricate next‐generation electronic devices. Organic–inorganic block copolymers form well‐ordered microphase separations with very small domain sizes. The design and preparation of a novel block copolymer consisting of syndiotactic polymethyl methacrylate (st‐PMMA) and polyhedral oligomeric silsesquioxane (POSS)‐functionalized polymethacrylate, designated as st‐PMMA‐b‐PMAPOSS, which can recognize functional molecules, are reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…The conventional poly(styrene‐ b ‐methyl methacrylate) is difficult to obtain domain spacing of less than 24 nm because Flory‐Huggins interaction parameter, χ , is not enough 22 . On the other hand, organic–inorganic hybrid block copolymer: at ‐PMMA‐ b ‐PMAPOSS could achieve the formation of domain spacing of 12 nm 8b . If this notion can be simply converted to an it ‐PMAPOSS‐ b ‐PMMA, strong repulsions between it ‐PMAPOSS and it ‐PMMA could take place.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional poly(styrene‐ b ‐methyl methacrylate) is difficult to obtain domain spacing of less than 24 nm because Flory‐Huggins interaction parameter, χ , is not enough 22 . On the other hand, organic–inorganic hybrid block copolymer: at ‐PMMA‐ b ‐PMAPOSS could achieve the formation of domain spacing of 12 nm 8b . If this notion can be simply converted to an it ‐PMAPOSS‐ b ‐PMMA, strong repulsions between it ‐PMAPOSS and it ‐PMMA could take place.…”
Section: Resultsmentioning
confidence: 99%
“…Various kinds of block copolymers containing‐POSS such as poly(styrene‐ b ‐PMAPOSS) (PS‐ b ‐PMAPOSS), 5 poly(ethylene oxide‐ b ‐PMAPOSS) (PEO‐ b ‐PMAPOSS), 6 and poly(trifluoroethyl methacrylate‐ b ‐PMAPOSS) (PTFEMA‐ b ‐PMAPOSS) were also prepared 7 . A previous study has reported the synthesis of PMMA‐ b ‐PMAPOSS, which exhibited a well‐ordered microphase separation with a minimum domain spacing of 12 nm 1c,8 …”
Section: Introductionmentioning
confidence: 99%
“…The so‐called reversible deactivation radical polymerization (RDRP) and living anionic polymerization are the powerful synthetic tools that have been successfully employed to achieve well‐defined POSS based hybrid (co)polymers of different composition and topologies . As an example, Hirai et al successfully polymerized POSS‐MA up to a degree of polymerization (DP) = 29 with a dispersity Ð –1.04 by living anionic polymerization that was successfully chain extended with styrene (S) and methyl methacrylate (MMA), subsequently affording well‐defined block copolymers, which could self‐assemble into hierarchical nanostructures .…”
Section: Introductionmentioning
confidence: 99%
“…The number-average molecular weight (M n ) and polydispersity index (Đ) were 8000 and 1.24, respectively. The stereoregularity of it-PMAPOSS was evaluated by using 13 C NMR spectroscopy. The signals at ∼45 ppm were assigned to meso− meso (mm), meso−racemo (mr), and racemo−racemo (rr) couplings from low to high magnetic field values, respectively.…”
mentioning
confidence: 99%